Lower-limb power cannot be estimated accurately from vertical jump tests - Tessier, J.-F.; Basset, F.-A.; Simoneau, M.; Teasdale, N. (Journal of Human Kinetics, 2013)
The countermovement jump test is often adopted to monitor lower-limb power of an individual. Despite several studies on the validity of this test, there is still a need to determine the minimal difference needed to be confident that a difference in power between two individuals is present or that a true change in the performance of an individual has occurred. In this study, power was measured from ground reaction forces and compared to that obtained from predictive equations for two groups of subjects (67 trained and 20 highly trained individuals). The height of each jump was determined with kinematic techniques. The main outcome is a large discrepancy between power calculated from ground reaction forces and that calculated from predictive equations. For the trained group, the R-square value between power and predicted power was 0.53 and the minimal difference to consider that two individuals were different was 821.7 W. For the highly trained individuals, a much larger R-square value was obtained (0.94). Despite this, the minimal difference to consider that two individuals were different was still large (689.3 W). The large minimal differences obtained raise serious concerns about using countermovement jumps for appraisal and monitoring of lower-limb power of an individual.